Response of broilers to dietary balanced protein. 1. Feed intake and growth - Azevedo, Jefferson Moraes [UNESP]; De Paula Reis, Matheus [UNESP]; Gous, Robert M.; De Paula Dorigam, Juliano César; Leme, Bruno Balbino [UNESP]; Sakomura, Nilva Kazue [UNESP] (CSIRO Publishing, 2021)
Context: Knowing the broilers' response to the intake of balanced protein allows nutritionists to choose the optimal level to be used in the feed. Aims: The objective of the present study was to describe the response of male and female broilers of two commercial strains to a range of dietary balanced protein levels. Methods: In total, 2496 sexed chicks (equal numbers of Ross 308 and Cobb 500) were used. Six dietary balanced protein levels × two strains × two sexes (24 treatments) were randomly allocated to 96-floor pens, using four replications of 26 chicks each. Feed intake, bodyweight, feed conversion efficiency, carcass weight and the weights of the breast without skin, thigh plus drum (leg) and wing were measured at 14, 28, 42 and 56 days of age. Key results: Feed intake in all periods in both strains and sexes increased as the dietary balanced protein level decreased, and then decreased markedly at the lowest balanced protein levels. Only at 14 days did the responses differ between strains and sexes; in all other cases, the responses differed only between sexes. At 14 days, the response in bodyweight differed between strains and sexes, whereas at all other samplings they differed only between sexes. The response in carcass, breast and wing yield at 14 days was the same for both strains and sexes but differed between strains and sexes at 28 days. At 42 and 56 days, the response differed only between sexes. The response in leg (thigh-plus-drum) weight at 14 days was the same for both strains and sexes, but after that differed between sexes only. Body lipid content increased linearly initially, and then quadratically, as dietary protein content was reduced. Conclusions: Appropriate equations are presented for describing the above responses of broiler chickens, male and female, from two commercial strains. Implications: The fitted equations may be used to calculate the optimum economic level of dietary balanced protein to be used under different economic circumstances.
Keywords: body lipid content; bodyweight; breast weight; feed intake; leg weight